Faktor-Faktor yang Mempengaruhi Jenjang Karir Tenaga Kerja Konstruksi dalam Perspektif Hukum Ketenagakerjaan(Literatur Review) - Muslimatul Mufida; Ismawati Ismawati; Muhammad Wahid Cahyana (Indo Publishing, 2026)
The construction sector is one of the largest labor absorbers in Indonesia, yet it still faces the problem of unclear career paths for its workers. This study aims to examine the factors influencing career paths for construction workers from a labor law perspective. The research method used was a literature review with a descriptive qualitative approach through a review of scientific articles, books, national regulations, and policy documents related to labor and construction services. The results indicate that career paths for construction workers are influenced by internal factors such as education, skills, work experience, motivation, and competency certification, as well as external factors such as working conditions, labor market needs, and regulatory support. From a labor law perspective, Indonesian laws and regulations essentially provide protection for career development through regulations on job training, competency certification, occupational safety and health, and the principle of non-discrimination. However, gaps remain between legal norms and field practice, primarily due to project-based employment relationships and weak oversight. Therefore, strengthening the implementation of labor law is key to ensuring the certainty and sustainability of career paths for construction workers in Indonesia.